Contribuição ao estudo da percepção da população sobre o comportamento de cães e gatos em 4 comunidades rurais de Mossoró/ RN - Costa, Vanessa Kaliane Nunes da Costa (2017)
Companion animals grow geometrically and the lack of proper control favors the increase of these animals in the streets. Neutering is an important alternative for controlling the populations of dogs and cats, contributing to the reduction of abandoned animals, zoonoses, ill-treatment and many diseases with society. However, there is a reluctance of many of the tutors of these animals to castrate them, since they associate sterilization with something negative, such as the emergence of behaviors considered as unwanted. Therefore, the present study aimed to make an analysis of the perception of the population on the behavioral changes of companion animals after the surgical sterilization procedure. The work was carried out on companion animals from the rural communities of Mossoró / RN. A survey of the number of animals from each community was carried out. At the time, a questionnaire was applied and the animals were registered, followed by castration by Surgical sterilization in those animals in which the tutors accepted. After 6 (six) months the questionnaires were reapplied. Through the data obtained with the reapplication of the questionnaires we obtained that the number of sociable dogs changed from 73.30% to 68.10%, whereas the cats were from 80.80% to 72.90%; 53.9% of the dogs had a habit of leaving home, later this value increased to 56, 8%, however the cats changed from 73.9% to 58.9%; 90.5% of the dogs were considered active, at reapplication this value changed to 89.9%, the cats initially presented a percentage of 84.3% and changed to 83.8%. 26.4% of the dogs had a habit of urinating in the corners or in the surroundings of the house, but this value changed to 22.90%, already of the 40% of felines that had this characteristic, only 14.3% maintained it. As for the habit of destroying objects, 31.6% of the dogs had this behavior, but after castration only 12.5% remained with it, for this characteristic cats changed from 22.20% to 6.25%. 20% of the dogs showed aggression, but this percentage changed to 10.8%, while 20% of the dogs were aggressive and only 12.1% continued. We can conclude tutors from the rural communities of Mossoró / RN are formed by a majority of low income financial farmers, who noticed changes in the behavior of dogs and cats, also observing a reduction in the number of cats present in the streets, but did not notice a change in the environmental conditions